Pengaruh Budaya Organisasi dan Komitmen Karyawan Terhadap Kinerja Pegawai di PT Lingkar Sakti Mas Banjarmasin - Kurniawan, Muhammad Aldo; Mardah, Siti; Amelia, Citra (Politeknik Sawunggalih Aji, 2025)
This study aims to analyze the influence of Organizational Culture and Employee Commitment on Employee Performance at PT Lingkar Sakti Mas Banjarmasin. The research employs a quantitative approach with 32 respondents, all of whom were selected using a saturated sampling technique. The data collection instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression. The results show that the Organizational Culture variable (X1) has a significant effect on Employee Performance (Y), with a t value of 5.475 > t table 2.042 and a significance level of 0.000 < 0.05. In contrast, the Employee Commitment variable (X2) does not significantly affect Employee Performance, with a t value of 1.731 < t table 2.042 and a significance level of 0.094 > 0.05. The simultaneous test (F test) indicates that Organizational Culture and Employee Commitment jointly have a significant effect on Employee Performance, as shown by an F value of 19.710 > F table 3.328 and a significance level of 0.000 < 0.05. In conclusion, improving employee performance can be achieved through the implementation of a strong organizational culture supported by consistent and balanced employee commitment.